AFFECTIVE DISCOURSE ANALYSIS AND SOCIAL MEDIA: METHODOLOGICAL INNOVATIONS IN THE CROSS-PLATFORM STUDY OF EMOTION AND RACE ON TWITTER, GAB, AND FACEBOOK - boler, megan (AoIR Selected Papers of Internet Research, 2021)
In the context of the so-called "post-truth" crisis, emotions have resoundingly replaced facts in our fast-moving, affectively-driven internet-based culture. Scholars are challenged to develop innovative methods for studying emotion and affect within studies of social media, and political communications. What is an effective interdisciplinary approach to the study of affect and communications in our rapidly-evolving media ecosystems? While the "affective turn" makes sense in the humanities, disciplines studying elections and populist sentiments traditionally draw upon quantitative and qualitative methods that tend to reduce and measure emotions as simply negative and positive. Further, political communications scholarship on "affective polarization" tend to define "in-groups" and "out-groups" solely in terms of partisan differences, missing much complexity of social identities and race relations. This three-year, funded research project draws from the politics of emotion to inform an innovative grounded theoretical study of emotional expression related to narratives of racism in social media. draw on Sarah Ahmed's concepts of sticky emotions and affective economies (2004) and Arlie Hochschild's concepts of feeling rules and deep stories (2016). This talk presents methodological innovations and research findings from our cross-platform digital ethnography of social media from Twitter, Gab, and Facebook, and qualitative discourse analysis of 1800 social media posts related to Black Lives Matter and the Capitol Riots. The paper provides a significant contribution to a nascent field of studies by specifically engaging an interdisciplinary theoretical framework that includes affect theory or politics of emotion alongside qualitative research of social media.